Optimizing Self Efficacy in High School Students Through Group Counseling with Rational Emotive Behavior Therapy (REBT) - Afasli, Bunga; Netrawati, Netrawati; Karneli, Yeni (JUPE : Jurnal Pendidikan Mandala, 2024)
Within the same age group, individuals have very different appearances, abilities, temperaments, interests and attitudes, including physical and mental differences. An educator must understand the individual differences of students to understand the desires, needs and problems of each student. Self-efficacy is self-confidence in carrying out tasks responsibly, considering one's own abilities, planning for the future, and having self-control when experiencing pressure and unpredictable situations. One method of guidance and counseling that can be relied upon to overcome problems faced by students is group counseling, especially Rational Emotive Behavior Therapy (REBT), which offers increased self-efficacy. This research aims to find out self-efficacy in high school students through the Rational Emotive Behavior Therapy (REBT) approach in group counseling. The research results show that self-efficacy has a very significant relationship with family social support and independent learning, adolescent adjustment, desire to learn, mathematics achievement, and communication skills.